2007
DOI: 10.1088/0031-9155/52/24/001
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic modelling of current flow in the heart from TASER devices and the risk of cardiac dysrhythmias

Abstract: Increasing use by law enforcement agencies of the M26 and X26 TASER electrical incapacitation devices has raised concerns about the arrhythmogenic potential of these weapons. Using a numerical phantom constructed from medical images of the human body in which the material properties of the tissues are represented, computational electromagnetic modelling has been used to predict the currents arising at the heart following injection of M26 and X26 waveforms at the anterior surface of the chest (with one TASER 'b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…These criteria would not necessarily imply any direct associated effects of the ECDs specifically on the heart. On the basis of modeling, Holden et al 45 and Sun and Webster 46 concluded that current densities generated by an ECD would be extremely low, and that ventricular fibrillation was highly unlikely to occur as a result of any direct effect of ECD pulses on the heart. Cao et al 47 also reported that a TASER X26 ECD application to a man, who had an implanted pacemaker, presumably caused ''ventricular myocardial capture" (retrospectively determined by reviewing data storage in the pacemaker).…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria would not necessarily imply any direct associated effects of the ECDs specifically on the heart. On the basis of modeling, Holden et al 45 and Sun and Webster 46 concluded that current densities generated by an ECD would be extremely low, and that ventricular fibrillation was highly unlikely to occur as a result of any direct effect of ECD pulses on the heart. Cao et al 47 also reported that a TASER X26 ECD application to a man, who had an implanted pacemaker, presumably caused ''ventricular myocardial capture" (retrospectively determined by reviewing data storage in the pacemaker).…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%
“…45,46 Cases reported in ketamine/xylazine-anesthetized animals. 48 May be associated with drug use, 38 but possibly only with existing heart abnormalities.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…[8][9][10][11][12] These theoretical analyses suggest that stun guns cannot deliver the amount of energy required to stimulate the heart or cause ventricular fibrillation. Most theoretical studies base their arguments on the following principles: only a small portion (4%-10%) of the current that reaches the chest will affect the heart 13 and the time constant of the cardiac cell membrane is much longer than the pulse duration generated by stun guns.…”
Section: Evidence That Stun Guns Cannot Stimulate the Heartmentioning
confidence: 99%
“…Human-head models are usually used for the characterisation of mobile terminal antennas when placed near to the head in talking position [5,16]. Whole-body voxel models with a spatial resolution as high as 1 mm 3 have been developed to represent humans of different physique and classify more than 30 different types of human body tissues [10,17]. CST Microwave Studio R has collaborated with Visible Human Project R and enables the import of Voxel Man which is based on a layered model obtained using a dissected male corpse [20].…”
Section: Introductionmentioning
confidence: 99%